Modernity, education young generation in the prospect of historical-pedagogical research - Bołdyrew, Aneta (EDUsfera. Ewa Jurczyk-Romanowska, 2019)
The aim of the article is to present in an aggregate way, the most important, especially significant for transformation of family life, youths and children’s educational situation, in the social transition in conditions of the modernity in the 19th and in the beginning of the 20th centuries
Keywords: childhood; education; modernity; family